2014
DOI: 10.1007/s13277-013-1502-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels and tissue expression of matrix metalloproteinase 2 (MMP-2) and tissue inhibitor of metalloproteinases 2 (TIMP-2) in colorectal cancer patients

Abstract: The objective of the study was the assessment of serum levels and tissue expression of matrix metalloproteinase 2 (MMP-2) and tissue inhibitor of matrix metalloproteinases 2 (TIMP-2) in patients with colorectal cancer (CRC). The study included 72 CRC patients and 68 healthy subjects. The serum levels of MMP-2 and TIMP-2 were measured using enzyme-linked immunosorbent assay (ELISA) method, whereas tissue expression of MMP-2 and TIMP-2 in cancer cells, interstitial inflammatory cells, and adjacent normal colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 29 publications
4
44
0
1
Order By: Relevance
“…For instance, increased TIMP-1 and TIMP-2 are associated with a poor prognosis in patients, which are produced by colon cancer cells and adjacent stroma cells. 4850 Notably, our data reveal for the first time that primary human MC are able to express and secrete both TIMP-1 and TIMP-2. In addition, uPAR expression, especially in tumor-associated stromal cells, is negatively associated with CRC patient survival 51 and MIF can promote intestinal inflammation and colonic carcinogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…For instance, increased TIMP-1 and TIMP-2 are associated with a poor prognosis in patients, which are produced by colon cancer cells and adjacent stroma cells. 4850 Notably, our data reveal for the first time that primary human MC are able to express and secrete both TIMP-1 and TIMP-2. In addition, uPAR expression, especially in tumor-associated stromal cells, is negatively associated with CRC patient survival 51 and MIF can promote intestinal inflammation and colonic carcinogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…These proteases facilitate cancer cell metastasis by degrading the basement membranes. Matrix metalloproteinase-2 (MMP-2) and MMP-9 play important roles in CRC and are considered to correlate with the prognosis of patients [4,5]. Decreased MMP-9 expression level was reported to associate with longer survival time and lower risk of cancer recurrence [6].…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes could, therefore, represent an appealing target for the proteolytic degradation of our microswimmers once they have completed their prescribed tasks. In a healthy individual, this enzyme is reportedly present at various concentrations, yet typically in the range of 140-200 ng mL -1 , depending on type of the tissue it is expressed (40,41). At an unrealistically high concentration of MMP-2, i.e., 100 µg mL -1 , we observed that the microswimmers were entirely degraded within an hour in vitro at 37 °C (Supplementary Movie 3).…”
Section: Biodegradability With Mmp-2mentioning
confidence: 81%